2021
DOI: 10.1177/21582440211014193
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Detailed Experience of Nightmare and Nightmare Disorder in Chinese University Students

Abstract: Nightmares influence the mental health of university students, but the prevalence of nightmare and nightmare disorder requires additional documentation. The data of detailed nightmare experience of nightmare disorder and related depressive mood in this population are also scarce. First, a total of 1,451 students in a comprehensive Chinese university were invited to report their nightmare frequency. Sixty-eight patients with nightmare disorder were diagnosed using a semi-structured clinical interview according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
1
4
1
Order By: Relevance
“…The prevalence of nightmare at 6% in this current study is comparable to the prevalence of 3% and 4.7% in India and China respectively. 17,41 Meanwhile, Schlarb et al in their study suggested that nightmare predicted insomnia very well contrary to the observation in our current study. 42 This is important as dream recalling has been previously reported to be the hallmark of REM sleep.…”
Section: Pattern Of Sleepcontrasting
confidence: 99%
“…The prevalence of nightmare at 6% in this current study is comparable to the prevalence of 3% and 4.7% in India and China respectively. 17,41 Meanwhile, Schlarb et al in their study suggested that nightmare predicted insomnia very well contrary to the observation in our current study. 42 This is important as dream recalling has been previously reported to be the hallmark of REM sleep.…”
Section: Pattern Of Sleepcontrasting
confidence: 99%
“…Contrasting to hypersomnia, both groups of Chinese students reported more serious nightmare problems than Japanese, consistent with a study revealing high level of nightmare experiences among Chinese university students (Wang et al, 2021). Interestingly, a very similar tendency to this was observed for experiences of negative life events.…”
Section: Discussionsupporting
confidence: 87%
“…The model emphasizes the cognitive-person variable (e.g., career self-efficacy) and how it interacts with personal or contextual factors to shape the course of career development. Interestingly, when examining the role of contextual factors on career outcomes, prior studies primarily examine either the parental input [16] or school input [17,18] on individuals' career outcomes. However, there is a lack of studies that compare the relative importance of these two important contextual variables on career outcomes (i.e., career self-efficacy or career doubt).…”
Section: Career Doubtmentioning
confidence: 99%
“…This is the first study to adopt the SCCT to critically evaluate this association. Moreover, since the majority of the studies examined the importance of either parental behaviors [16] or school factors [17,18] to support career outcomes, studies that examine and compare the relative importance of parental and school support in relation to career doubt are scarce. This study evaluates the relative importance of contextual and individual factors and thus fills a research void on career doubt.…”
Section: Theoretical Contributionsmentioning
confidence: 99%